RANCANG BANGUN MESIN MIXER PUPUK ORGANIK - Yosua Guntur silambi; Daud P. Mangesa; Yeremias M. Pell (Universitas Nusa Cendana, 2025)
Organic fertilizers are fertilizers composed of living matter, such as weathering of animal and human plant residues. Organic fertilizers have more organic matter than nutrient content. Organic fertilizers have the advantage of being environmentally friendly, providing nutrients and macro elements for plants, functioning as soil dividers, improving soil structure, improving soil pore size which in turn makes water holding capacity and soil aeration better. Raw materials that can be used in making organic fertilizers include animal manure, rice husks, soil and charcoal. making organic fertilizer is a very heavy job and requires a long time to produce organic fertilizer until it is ready to use if done manually. This is what encourages research to increase the author's knowledge in the research “DRY ORGANIC PUPUK MIXER MACHINE DESIGN” in order to help make it easier to produce organic fertilizer in the next two decades